Behavior of hybrids, improved varieties and native varieties of yellow corn in Chiapas - Coutiño-Estrada, Bulmaro; Rincón-Espinosa, David; Ramírez-Díaz, José Luis; Reyes-Méndez, César Augusto; Espinosa-Calderón, Alejandro; Tadeo-Robledo, Margarita (Revista Mexicana de Ciencias Agrícolas, 2026)
In 2016, Mexico imported almost 13 million tons of yellow corn, valued at more than 2.3 billion dollars. However, imports could be reduced or eliminated if the yellow-grained varieties and hybrids generated by the National Institute of Forestry, Agricultural and Livestock Research were grown. The study aimed to identify the best hybrid and the best variety of yellow corn that the National Institute of Forestry, Agricultural and Livestock Research has released for the Mexican tropics, where more than 420 000 ha are planted, and 2.1 million tons of yellow corn are produced. During the spring-summer agricultural cycle of 2018, 21 genotypes were evaluated in three localities in Chiapas; the hybrids H-443A, REMACO15A and H-386A stood out statistically with grain yields of 5.748, 5.608, and 5.514 t ha-1 and equaled two of the control commercial hybrids; of the improved varieties, Población Amarilla C1 stood out with 4.9 t ha-1 and of the native varieties, the Olotillo Amarillo-1 variety, from Ocozocoautla, stood out with 3.1 t ha-1.
Keywords: elite trials; genetic improvement